Firefighter hemodynamic responses to different fire training environments. (June 2021) - Lefferts, Elizabeth C; Rosenberg, Alexander J; Grigoriadis, Georgios; Wee, Sang Ouk; Kerber, Stephen; Fent, Kenneth W; Horn, Gavin P; Smith, Denise L; Fernhall, Bo
Firefighting is associated with an increased risk for a cardiovascular (CV) event, likely due to increased CV strain. The increase in CV strain during firefighting can be attributed to the interaction of several factors such as the strenuous physical demand, sympathetic nervous system activation, increased thermal burden, and the environmental exposure to smoke pollutants. Characterizing the impact of varying thermal burden and pollutant exposure on hemodynamics may help understand the CV burden experienced during firefighting. The purpose of this study was to examine the hemodynamic response of firefighters to training environments created by pallets and straw; oriented strand board (OSB); or simulated fire/smoke (fog). Twenty-three firefighters had brachial blood pressure measured and central blood pressure and hemodynamics estimated from the pressure waveform at baseline, and immediately and 30 minutes after each scenario. The training environment did not influence the hemodynamic response over time (interaction, p > 0.05); however, OSB scenarios resulted in higher pulse wave velocity and blood pressure (environment, p < 0.05). In conclusion, conducting OSB training scenarios appears to create the largest arterial burden in firefighters compared to other scenarios in this study. Environmental thermal burden in combination with the strenuous exercise, and psychological and environmental stress placed on firefighters should be considered when designing fire training scenarios and evaluating CV risk.